Crystal structures of three classes of non-steroidal anti-inflammatory drugs in complex with aldo-keto reductase 1C3. - Jack U Flanagan (PLoS ONE, 2012)
Aldo-keto reductase 1C3 (AKR1C3) catalyses the NADPH dependent reduction of carbonyl groups in a number of important steroid and prostanoid molecules. The enzyme is also over-expressed in prostate and breast cancer and its expression is correlated with the aggressiveness of the disease. The steroid products of AKR1C3 catalysis are important in proliferative signalling of hormone-responsive cells, while the prostanoid products promote prostaglandin-dependent proliferative pathways. In these ways, AKR1C3 contributes to tumour development and maintenance, and suggest that inhibition of AKR1C3 activity is an attractive target for the development of new anti-cancer therapies. Non-steroidal anti-inflammatory drugs (NSAIDs) are one well-known class of compounds that inhibits AKR1C3, yet crystal structures have only been determined for this enzyme with flufenamic acid, indomethacin, and closely related analogues bound. While the flufenamic acid and indomethacin structures have been used to design novel inhibitors, they provide only limited coverage of the NSAIDs that inhibit AKR1C3 and that may be used for the development of new AKR1C3 targeted drugs. To understand how other NSAIDs bind to AKR1C3, we have determined ten crystal structures of AKR1C3 complexes that cover three different classes of NSAID, N-phenylanthranilic acids (meclofenamic acid, mefenamic acid), arylpropionic acids (flurbiprofen, ibuprofen, naproxen), and indomethacin analogues (indomethacin, sulindac, zomepirac). The N-phenylanthranilic and arylpropionic acids bind to common sites including the enzyme catalytic centre and a constitutive active site pocket, with the arylpropionic acids probing the constitutive pocket more effectively. By contrast, indomethacin and the indomethacin analogues sulindac and zomepirac, display three distinctly different binding modes that explain their relative inhibition of the AKR1C family members. This new data from ten crystal structures greatly broadens the base of structures available for future structure-guided drug discovery efforts.